DISEMINASI DAN PELATIHAN TEKNOLOGI ALAT INTEGRATED EMBEDDED SENSING SYSTEMS BAGI UKM SATE BANDENG AWAL PUTRA MANDIRI DI KOTA SERANG - Denny, Yus Rama; Assaat, Lusiani Dewi; Perdana, Fachruddin; Gustiono, Vaka (Bahasa Indonesia, 2023)
UKM Awal Putra Mandiri is an activist for the city of Serang's superior product Sate Bandeng so that it can develop by seeing a sustainable business opportunity by exploiting existing potential. UMKM Sate Bandeng Awal Putra Mandiri, is one of the UMKMs that provides Sate Bandeng products and has product supplies at the national level. The results obtained from the discussion contained problems that were experienced, namely that technology had not been implemented which was able to detect the freshness and content of dangerous substances in milkfish raw materials in a real-time, practical manner. This Community Service activity includes dissemination and training on Integrated Embedded Sensing System technology products for detecting the level of freshness of food ingredients and the content of dangerous substances. The implementation of Community Service activities runs well and smoothly, so that employees and UKM owners are very interested in using technological tools. Apart from that, this activity can reduce the costs incurred by UKMs due to mistakes in buying fish that is not fresh.. Abstrak UKM Awal Putra Mandiri merupakan penggiat produk unggulan kota Serang Sate Banden g sehingga dapat berkembang dengan melihat suatu peluang usaha yang berkesinambungan dengan memanfaatkan potensi yang ada. UMKM Sate Bandeng Awal Putra Mandiri, menjadi salah satu UMKM yang menyediakan produk Sate Bandeng dan memiliki pasokan produk ke tin gkat nasional. Hasil yang didapatkan dari diskusi terdapat permasalahan yang di alami yaitu belum diterapkan teknologi yang mampu mendeteksi kesegaran dan kandungan zat berbahaya pada bahan baku ikan bandeng yang real- time, dan praktis. Kegiatan Pengabdian Masyarakat inimeliputi diseminasi dan pelatihan produk teknologi Integrated Embedded Sensing System untuk deteksi tingkat kesegaran bahan pangan dan kandungan zat berbahaya. Pelaksanaan kegiatan Pengabdian Masyarakat berjalan dengan baik dan lancar, sehingga para karyawan dan owner UKM sangat tertarik dengan menggunakan alat teknologi. Selain itu, dari kegiatan tersebut mampu menekan biaya pengeluaran UKM untuk kesalahan membeli ikan yang tidak segar.